MISCONCEPTION ANALYSIS OF MATH CLASS VII USING THREE TIER-TEST: ANALISIS MISKONSEPSI MATERI MATEMATIKA KELAS VII MENGGUNAKAN THREE TIER-TEST - Akmal Riswandi; Nursalam; Baharuddin (MaPan : Jurnal Matematika dan Pembelajaran, 2022)
This study aims to find out what misconceptions are experienced by students in mathematics material for class VII SMP and to find out what factors cause students' misconceptions in mathematics material for class VII SMP. This type of research is qualitative research using a descriptive method. The research subjects in this study were 8 students of class VII B students of SMPN 46 Makassar with data collection techniques consisting of three tier-test diagnostic tests, interviews, and documentation. Data analysis techniques in this study consisted of data reduction, data presentation, and conclusion drawing. The results of this study indicate that based on the results of the Three Tier-Test given to class VII B students, it was identified that students experienced misconceptions in algebraic material with the categories of misconceptions and misconceptions (false positive). The majority of misconceptions occur in all algebraic materials, namely: algebraic concepts, algebraic elements, addition operations, subtraction operations, multiplication operations, and division operations. In addition, it was also found that the factors causing the misconceptions of class VII B students of SMPN 54 Makassar, namely the lack of students' ability to understand algebraic concepts in-depth, lack of interest in learning specifically for algebra students, the method often used by teachers, namely the lecture’s method, these making students difficult to understand algebraic material and pre-algebraic concepts.